Encyclopedia of Arkansas Music - Keckhaver, Mike; Welky, Ali (Book collections on Project MUSE., 2013)
"'Encyclopedia of Arkansas Music' is a special project of the Encyclopedia of Arkansas History & Culture (EOA), an online encyclopedia launched in 2006 by the Butler Center for Arkansas Studies at the Central Arkansas Library System. This colorful, photo-filled reference work spanning all aspects of Arkansas's musical past and present includes more than 150 entries on musicians, ensembles, musical works, and events."--Publisher description